Environmental Perspective Management in Utilizing Mangrove Forest Resources for Community Welfare - Bekti Utomo (Yayasan Putra Adi Dharma, 2024)
The community service aims to raise awareness of the importance of sustainable utilization of mangrove forest resources through environmentally conscious management. Through a participatory approach involving local communities, local governments, and non-governmental organizations, the identification of dominant mangrove species, mapping of critical areas, and development of sustainable management plans are conducted. Through education, training, and field socialization activities, communities are empowered to understand the ecological and economic benefits of mangrove forests as well as environmentally friendly management techniques. The result is an increased awareness of the importance of preserving mangrove forests and their sustainable utilization, while creating economic and social benefits for the local community. Active community involvement in management enhances the longterm sustainability of this project.